A Psychosexual Rehabilitation Booklet Increases Vaginal Dilator Adherence and Knowledge in Women Undergoing Pelvic Radiation Therapy for Gynaecological or Anorectal Cancer: A Randomised Controlled Trial. Issue 2 (February 2019) - Lubotzky, F.P.; Butow, P.; Hunt, C.; Costa, D.S.J.; Laidsaar-Powell, R.; Carroll, S.; Thompson, S.R.; Jackson, M.; Tewari, A.; Nattress, K.; Juraskova, I.
Abstract: Aims: Women treated with pelvic radiation therapy (PRT) for gynaecological or anorectal cancer report a high number of sexual problems and unmet post-treatment psychosexual information needs. Currently, there is suboptimal adherence to recommended rehabilitation aids, such as vaginal dilators, and a paucity of resources to facilitate post-radiation rehabilitation and reduce distress in this population. This randomised controlled trial aimed to evaluate the effectiveness of a study-developed psychosexual rehabilitation booklet in this setting. Materials and methods: Eighty-two women scheduled for PRT to treat gynaecological/anorectal cancer were randomised to receive the intervention booklet ( n  = 44) or standard information materials ( n  = 38). Self-report questionnaires administered at pre-treatment baseline and at 3, 6 and 12 months post-treatment assessed adherence with rehabilitation aids, booklet knowledge, anxiety, depression and sexual functioning/satisfaction. Results: Dilator adherence and booklet knowledge were significantly higher in the intervention group than in the control group (averaged over time points), with scores significantly increasing over time. Younger age and gynaecological cancer were significant predictors of greater dilator adherence. No significant group differences were found on psychological and sexual measures. Conclusions: The psychosexual rehabilitation booklet was effective in educating women with gynaecological and anorectal cancers about PRT-related psychosexual side-effects and rehabilitation options, as well as promoting uptake of vaginal dilator use. Future research should elucidate the effectiveness of this booklet in women with greater psychological and sexual functioning needs. Highlights: Patients had significantly greater adherence to vaginal dilator recommendations. They had increased post-treatment rehabilitation knowledge across time points. Intervention could facilitate pelvic examination. It can improve detection of new or recurrent cancer. It can improve psychosexual adjustment in this population.